1999
DOI: 10.1093/bja/82.3.402
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane inhibits neuronal Ca2+ channels through enhancement of current inactivation

Abstract: To help clarify the mechanisms by which volatile anaesthetics act on neuronal Ca2+ channel currents (IBa), the effects of isoflurane were studied on IBa in rat dorsal root ganglion (DRG) cells. Voltage-dependent IBa were pharmacologically subdivided into L-, N- and P/Q-types, and toxin-resistant IBa. At clinically relevant concentrations, isoflurane inhibited the L-, N- and P/Q-types, but not toxin-resistant IBa. The IC50 values for the L-, N- and P/Q-types were 0.7%, 1.3% and 3.0%, respectively (concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…These drugs decrease the amplitude of both peak and residual (similar to "end current" here) Ca 2ϩ currents, shift Ca 2ϩ current inactivation to hyperpolarizing potentials, and increase the inactivation rate of native VSCCs in hippocampal (Study, 1994) and dorsal root ganglion neurons (Kameyama et al, 1999) as well as VSSC-expressed in oocytes (Kamatchi et al, 1999). One difference between the VOCs and volatile anesthetics is the ability of the former to shift the activation potential to more hyperpolarized potentials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These drugs decrease the amplitude of both peak and residual (similar to "end current" here) Ca 2ϩ currents, shift Ca 2ϩ current inactivation to hyperpolarizing potentials, and increase the inactivation rate of native VSCCs in hippocampal (Study, 1994) and dorsal root ganglion neurons (Kameyama et al, 1999) as well as VSSC-expressed in oocytes (Kamatchi et al, 1999). One difference between the VOCs and volatile anesthetics is the ability of the former to shift the activation potential to more hyperpolarized potentials.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol and volatile anesthetics have been demonstrated to disrupt function of VSCCs (Study, 1994;Kamatchi et al, 1999;Kameyama et al, 1999;McMahon et al, 2000), and this action has been suggested to contribute to effects of these compounds on the nervous system. The present studies were designed to test further the hypothesis that VOCs interact with VSCCs.…”
mentioning
confidence: 99%
“…Taken together, this suggests that the halothane-induced decrease in mEPSC and mIPSC frequency may be the result of a reduction in presynaptic calcium channel activity or by an interference with the calciumdependent proteins that mediate vesicular-membrane fusion. It was indeed shown that various types of voltage-gated calcium channels were inhibited by volatile anesthetics such as halothane and isoflurane and intravenous anesthetics such as propofol (Asahina et al, 1998;Nikonorov et al, 1998;Hirota et al, 1999;Kamatchi et al, 1999Kamatchi et al, , 2001Kameyama et al, 1999;McDowell et al, 1999;Camara et al, 2001;Hü neke et al, 2001;Yamakage and Namiki, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Isoflurane and sevoflurane significantly decreased the inward currents through L-type voltage-dependent Ca 2+ -channel and inhibited the porcine tracheal smooth muscle contraction (13). Isoflurane also inhibited the voltagedependent Ca 2+ -channels through enhancement of current inactivation in rat dorsal root ganglion cells (14). The inhibitory effects of general anesthetics on storeoperated Ca…”
Section: +mentioning
confidence: 95%